Progress Report for the Uttarakhand Third Five Year Plan 1963-64 - Planning Commission (Planning Commission, 1963)
Expansion of Multi-purpose Horticulture Farms—All the 11 existing Horticulture Farms and newly established 6 small farms (5 in Pithoragarh and 1 in Uttarkashi districts) at the Block Headquarters continued to function. Efforts are being made to acquire suitable land for establishing 15 small farms more at the remaining Block Headquarters (3 in PTH, 9 in CHI and 3 in UKI) of the Uttarakhand Division.
Uttarakhand